Research on the influence of foaming gas in compressed air/nitrogen foam on extinguishing the n-heptane tank fire. (September 2021) - Wang, Kun; Fang, Jun; Shah, Hassan Raza; Lang, Xuqing; Mu, Shanjun; Zhang, Yongming; Wang, Jingwu
Abstract: Tank fires threaten the lives of people and pollute the environment for their intense radiant heat, rapid fire spread and explosion hazard. Compressed air/nitrogen foam (CAF/CNF), a cleaner fire extinguishing technique used for the tank fire suppression because halogen-based agents were prohibited for environmental reasons. In this work, the influence of foaming gas in CAF/CNF on extinguishing the n-heptane tank fire was firstly investigated. Firstly, it was found that CNF spreads faster with rapid increase in foam thickness, mainly due to its better stability and less evaporation. Secondly, after foam was discharged, there existed a short increase of the combustion intensity, associated with three monotonous regions and two time delays in the whole extinguishing time. The two time delays were caused by Rayleigh–Taylor instability and flame sheet shift, respectively, and the shift distance was larger for CNF. Finally, the influential factors contributing to flame extinction were exhibited to be mainly related to the decrease in liquid burning rate and gas-phase Damkohler number. Among these factors, foam spreading rate and thickness dominated due to coupled chemical and physical extinguishing effects. Resulted from some competitive effects, CNF was slightly more efficient at extinguishing tank fires than CAF. Graphical abstract: Image 1 Highlights: Different flame characteristic variation induced by CAF and CNF was investigated. Three monotonous regions and two time delays were found in the extinguishing time. CNF spreads faster with the rapid increase of the foam thickness than that of CAF. There existed a short increase of the combustion intensity after foam discharge. There are some competitive factors making CNF extinguishing efficiency higher.